PENDIDIKAN DASAR : PEMBANGUNAN MANUSIA BERKUALITAS DALAM MDGS 2015 - Meydianawathi, Luh Gede (INPUT Jurnal Ekonomi dan Sosial; Vol. 1, No. 2 Agustus 2008)
The obligation to prepare human capital which is started from the early age through the government program “Wajib Belajar 9 Tahun” will take longer time than it should. This effort is not equal with human manufacturing because human can not be developed instantly. A human should be developed in more quali? ed steps dan sustainable to be exactly become intelligence, quali? ed and dynamic human. With some proper indicators for instance School Enrollment Ratio, Literacy and the amount of drop out student, each region in Indonesia could count their own readiness to implementing the agreement of Millenium Development Goals (MDGs), which is all the primary aged student whether they are boys or girls, in the whole part of the world deserve to access school in the year of 2015.
Keywords: primary education, School Enrollment Ratio, Literacy, Drop Out Student, MDGs